Effect of heat and humidity on time-trial performance in Australian National Team road cyclists - Martin, D. T.; Tatterson, A.; Lee, H.; Boston, T.; Hahn, A. G.; Febbraio, M. A. (Medicine & Science in Sports & Exercise, 1997)
Effects of hot humid conditions on cycling performance were investigated using 11 members of the Australian National Road Cycling Squad. One week following assessment of various physiological factors, Ss completed two, maximal 30-min cycling time-trials in an environmental chamber set at 32 degrees Celsius (60% relative humidity) or 23 degrees Celsius (60% relative humidity) with a 20 km/hr head wind. Mean power output was reduced by 6.5% in the hot condition but rectal temperatures were similar. Heart rates climbed faster in the hot condition but peak heart rates were the same in both conditions. Blood lactate was higher and pH and bicarbonate lower earlier in the hot condition but at the end of the time-trial lactate was lower and pH and bicarbonate were higher than in the moderate temperature condition. In hot conditions, elite cyclists reduced performance despite a consistent core body temperature. Implication. During exercise in hot humid conditions, elite cyclists select a level of power-output that will allow them to remain below an excessive body core temperature. Experienced elite athletes appear to have a self-regulatory mechanism for accommodating the stress of heat while performing.